Ambroży o starości w swoich listach - Wysocki, Marcin (Vox Patrum, 2011)
The correspondence of St Ambrose, of which 91 letters survive, provides a picture of his pastoral and social activities. His letters were directed to people of differing ages and classes; in some of them one can find his views on ageing, its features and dangers and how the old should be cared for. The period of old age is, according to the Bishop of Milan, the period of becoming a perfect men. Ambrose considered that with advancing age man grows towards perfection and maturity in the human sense, but more importantly in the moral and religious sense. He taught that everyone must try to improve themselves gradually throughout life by conversion and repentance, achieving maturity and perfection by the time of death.